Implementasi Algoritma Genetika Pada Penempatan Tugas Asisten Laboratorium Berbasis Web - Adhi Kusnadi; David Setyadi Santoso (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
On education system in University, the given subject is not only theoretics subject, but practicum also. In teaching practical subjects, the lecturer often experiences a difficulty to answer and handle every question that the students have in laboratory. Therefore, the assistant laboratory is needed here. One of the division in Universitas Multimedia Nusantara, ICT LAB still arranges the assignment of the assistant laboratory manually. It is difficult and takes some times. This thing becomes the reason for the development of an application ICT LAB that can do the assignment process automatically. This research is using Genetic algorithm that can calculate fitness value which show the matching level of the assignment that has been created. Based on the testing, using one point crossover, mutation on bit level, and rank selection, the average fitness value is 68.571% from all of the laboratory assistant vacancy. Based on the data used, there are 22 assignment slots on certain subjects that don’t have any applicant. So if that 22 slots are not used in the fitness calculation, there are only 118 assignment slot and the fitness value becomes 80,5%. This fitness value has problem with the quantity of student that didn’t fit to all of the assignment slot. Index Terms - Genetic Algorithm, rank selection, one point crossover, assignment, laboratory assistant.